2015
DOI: 10.4236/jtst.2015.13011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different Washing Effects on Physical and Mechanical Properties of Cotton Knitted Garments

Abstract: This paper deals with three types of washing (enzyme, softener, Silicone) effects on 100% cotton Single Jersey T-shirt, Slub Single Jersey T-shirt, Double Lacoste (5% Lycra) Polo shirt, Single jersey CVC (T-shirt) and PC single Jersey (T-shirt). Typical industrial washing procedures and techniques were followed and then physico-mechanical properties were analyzed under standard condition. It is observed that after washing, weight of each garments has increased from 5% to 36%; stitch length of the constituted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…The results showed that when enzyme wash was applied on the knit garments, it improved all the tested properties of knit garments, and it also reduced the hairy fibers from the fabric surface. Similar results were found in case of Silicone and softener wash as well [29].…”
Section: Introductionsupporting
confidence: 86%
“…The results showed that when enzyme wash was applied on the knit garments, it improved all the tested properties of knit garments, and it also reduced the hairy fibers from the fabric surface. Similar results were found in case of Silicone and softener wash as well [29].…”
Section: Introductionsupporting
confidence: 86%
“…Modern engineering demands for avant-garde materials along with astute designs [1]. Washing of garments, more specifically denim products, has become increasingly popular due to its modifying outlook and appearance [2][3][4]. Conducting such a process requires huge amount of water and chemical which significantly pollutes the environment [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of burst strength about 10% is considered acceptable. [18]. So, the loss of burst resistance of single jersey and interlock is acceptable.…”
Section: Effects Of Enzymatic Treatment On Burst Resistancementioning
confidence: 99%